Elimination of Mitochondrial DNA from Mammalian Cells. Issue 1 (9th April 2018) - Khozhukhar, Natalya; Spadafora, Domenico; Rodriguez, Yelitza; Alexeyev, Mikhail
Abstract: To cope with DNA damage, mitochondria developed a pathway by which severely damaged or unrepairable mitochondrial DNA (mtDNA) molecules are abandoned and degraded, and new molecules are resynthesized using intact templates, if available. In this unit, we describe a method that harnesses this pathway to completely eliminate mtDNA from mammalian cells by transiently overexpressing the Y147A mutant of human uracil‐ N ‐glycosylase (mUNG1). We also provide an alternate protocol for mtDNA depletion using combined treatment with ethidium bromide (EtBr) and dideoxycytidine (ddC). Support protocols detail approaches for (1) genotyping ρ° cells of human, mouse, and rat origin by PCR; (2) quantitation of mtDNA by quantitative PCR (qPCR); and (3) preparation of calibrator plasmids for mtDNA quantitation. © 2018 by John Wiley & Sons, Inc.